Copper(II) complexes derived from furfurylamine and thiophenyl ligands: cytotoxicity, antioxidant properties, and molecular docking assessments. (15th January 2022) - Siqueira, Josiéli Demetrio; de Pellegrin, Sidnei Flores; Fontana, Liniquer André; Iglesias, Bernardo Almeida; Sagrillo, Michele Rorato; Oliveira, Pâmella Schramm; Rossato, Aline; da Silva Fernandes, Liana; Neves, Ademir; Chaves, Otávio Augusto; Back, Davi Fernando
Graphical abstract: Copper(II) complexes obtained through the condensation of aromatic aldehydes and furfurylamine/thiophenyl were tested in vitro in antioxidant and cytotoxicity assays on biomolecules such as CT-DNA in addition to evaluating by molecular coupling. Abstract: This manuscript describes the synthesis, structural analysis, antioxidant evaluation, cytotoxicity, interaction with DNA, and molecular docking modeling of copper(II) complexes derived from aromatic aldehydes and amines containing furyl and thiophene fragments (C1-C5 ). All compounds were tested as catalytic mimetics of superoxide dismutase (SOD) using the NBT photoreduction method in a pH 7.8 buffer solution, and structural analysis revealed that all complexes had a quadratic geometry. However, there were important differences in the evaluations with CT-DNA interaction, antioxidant activity, and cytotoxic characteristics. The main interest was to correlate the structure obtained by X-ray diffraction with the tested activities, adding relevant information for future and even deeper applications.